Determinants of Performance Systemic Banks in Indonesia - M. Noor Salim and Firman Julian (International Journal of Advanced Science and Technology, 2020)
The aim of this study was to analyze factors which influence Indonesia Systemic Bank Performance and Its Impact on Customer Trust. The researche will help in determining what increases Indonesia Systemic bank performance. The independent variable of this study uses the financial ratio of Non Performing Loans (NPL), Cost Income Ratio (CIR), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR). Performance measured by Return on Assets (ROA) indicator, and for the Customer Trust variable measured by Bank Rating indicator. The study used panel data analysis and the process was using Eviews version 9.0. The results of the analysis in this study indicate that (1) NPL has a negative and not significant effect on ROA, (2) CIR has a negative and significant effect on ROA, (3) NIM has a positive and significant effect on ROA, (4). CAR has a negative and not significant effect on ROA, (5) NPL, CIR, NIM and CAR simultaneously have a positive and significant effect on ROA, (6) NPL has a positive and not significant effect on Rating. (7) CIR has a negative and not significant effect on Rating, (8) NIM has a negative and significant effect on Rating. (9) CAR has a positive and not significant effect on Rating, (10) NPL, CIR, NIM and CAR simultaneously have a positive and significant effect on Rating, (11) ROA has a negative and not significant effect on Rating.